Molar Changes With a Normal Viable Fetus: A Case Report - Marjaneh Farazestanian; Asieh Maleki; Somayeh Bolandi; Zohreh Yousefi; Malihe Hasanzadeh; Laya Shirinzadeh; Sara Kamandi (Tehran University of Medical Sciences, 2020)
Objective: The presence of a normal fetus with normal karyotype accompanied by molar changes in the placenta is a rare condition, which carries a significant risk to the mother and fetus. There is a controversy regarding the proper management of this condition. Here, we present the case of a singleton pregnancy that showed molar changes in the pathological study of the placenta, but ended up with a normal viable neonate. Case Report: A 23-year-old primigravida woman, with a 3-year history of infertility, presented with vaginal bleeding and spotting. Her ß-human chorionic gonadotropin (HCG) at 13th week was 36500 mIU/ml. Serial sonography assessments were suggestive for molar changes and a normal fetus with growth retardation but normal Doppler assessment. The patient underwent elective Cesarean section at 37 weeks gestation and a healthy female neonate with an Apgar score of 9-10, weighing 2270 g was born. Pathological assessment of the placenta confirmed the diagnosis of incomplete hydatidiform mole. After two months, the mother had no complications, her ß-HCG level was untraceable, and the infant was in good condition. Conclusion: Despite being a rare condition, partial moles can be accompanied by delivery of a normal fetus. The management of this condition still remains challenging and should be done under close monitoring with extreme caution.